1994
DOI: 10.1007/bf01707661
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial bacteremia in a medical-surgical intensive care unit: Epidemiologic characteristics and factors influencing mortality in 111 episodes

Abstract: Epidemiology and etiology of ICU-acquired bacteremia does not differ seriously in respect to nosocomial bacteremia among unselected populations, although it is associated with a greater incidence and overall mortality. Presence of shock is the most important modificable variable affecting the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
4
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(74 citation statements)
references
References 38 publications
7
59
4
4
Order By: Relevance
“…No significant differences were found for other variables analyzed. In other studies, several factors have been described as predictive of mortality in patients with CVC-related BSI, such as adult respiratory distress syndrome, shock, multiorgan failure, mechanical ventilation, chronic hepatic failure, acute renal failure and APACHE II score greater than 14 (Rello et al, 1994;Valles et al, 1997;Garrouste-Orgeas et al, 2006). Unlike these studies, we could not find an association of mortality with admission APACHE II score.…”
Section: Discussioncontrasting
confidence: 98%
“…No significant differences were found for other variables analyzed. In other studies, several factors have been described as predictive of mortality in patients with CVC-related BSI, such as adult respiratory distress syndrome, shock, multiorgan failure, mechanical ventilation, chronic hepatic failure, acute renal failure and APACHE II score greater than 14 (Rello et al, 1994;Valles et al, 1997;Garrouste-Orgeas et al, 2006). Unlike these studies, we could not find an association of mortality with admission APACHE II score.…”
Section: Discussioncontrasting
confidence: 98%
“…Data based on literature 25,26 showed overall mortality around 30%, similar to the fi ndings in our study. However, it was observed that among patients who presented sepsis, 50% died by the thirtieth day after diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…However, it was observed that among patients who presented sepsis, 50% died by the thirtieth day after diagnosis. Data published in Spain in 1993 26 presented a mortality rate of 65.7%, straightly linked to sepsis. Mortality rate due to sepsis in BASES study was 33.9%, 27 whereas Brun-Buisson et al 20,28 observed death probability of 25% by the 28th day.…”
Section: Discussionmentioning
confidence: 99%
“…7,14,18,22,24,26,36,42,43,45,51,[64][65][66][67] In a comparison between the former East and West Germany, Rüden et al 68 found a lower prevalence of nosocomial infections in the former East German states, mainly due to a lower use of devices. An estimated 5 million central venous catheters are inserted into patients in the United States each year, 69 but it is difficult to measure how much the utilization of infusion IV devices has increased in recent years.…”
Section: Discussionmentioning
confidence: 99%